PERSEPSI MAHASISWA UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI TERHADAP PERKULIAHAN DARING SEBAGAI SARANA PEMBELAJARAN SELAMA MASA KARANTINA COVID-19 - MUHAMMAD NURMAN (Universitas Pahlawan Tuanku Tambusai, 2020)
Online lectures is one form of internet utilization that can enhance the role of students in the learning process. Descriptive analysis in this study examines students' perceptions of the University Pahlawan Tuanku Tambusai on online learning models related to the use of media, learning styles, and certain types of communication that are popular with students to help them get better output from online learning activities. The number of samples in this study were 806 students of the University Pahlawan Tuanku Tambusai who had been involved in online learning during the Covid-19 quarantine period. The results found that the most popular online learning media are Google Classroom. As many as 89,1% of University Pahlawan Tuanku Tambusai students are familiar with various online learning media before online lectures begin. In addition, the communication pattern that is most popular by students is the semi-two-way pattern. Further research is needed on online learning research with problem- based, collaborative, and other models.